Teacher Strategies in Building Student Engagement through Interactive and Contextual Methods in Islamic Religious Education at SMP Negeri 6 Batang Hari - Riski Ridwansah; Jamilah (Lembaga Bale Literasi, 2025)
This qualitative descriptive study examined the strategies employed by an Islamic Religious Education (PAI) teacher in building student engagement through interactive and contextual learning methods at SMP Negeri 6 Batang Hari. Data were collected through classroom observation, interviews with the teacher, the principal, and students, and analysis of lesson plans and teaching documentation, then analyzed using the interactive model of Miles and Huberman. The findings show that the teacher applied student-centered lesson planning, interactive techniques such as discussion, cooperative grouping, question-and-answer sessions, and educational games, alongside a contextual approach that linked material to students' daily experiences in honesty, charity, and social behavior. Instructional media, positive motivation, and appreciation for student opinions further strengthened participation and classroom confidence. Obstacles included unequal academic ability, low self-confidence among some students, limited time, phone-related distraction, and restricted technological facilities, which the teacher addressed through differentiation, individual mentoring, and heterogeneous grouping. The study concludes that combining interactive and contextual strategies effectively enhances student engagement while supporting the internalization of Islamic values in daily conduct.